FREQUENCY OF ATONIC UTERUS DUE TO PRIMARY POSTPARTUM HEMORRHAGE: A CROSS-SECTIONAL STUDY - Sahak, Mahbooba; Kurmanova, Almagul Medeubaevna (Interdisciplinary Approaches to Medicine, 2021)
Postpartum hemorrhage (PPH) is loss of 500 mL of blood from genital tract after normal vaginal delivery or 1000 mL after cesarean section. PPH is one of an important cause of maternal mortality and morbidity worldwide, the only strategy that has shown a significant reduction in maternal mortality in patients with PPH is active treatment and management of third stage of labor.In this study we aim to determine the frequency of atonic uterus due to postpartum hemorrhage.A descriptive cross-sectional study was carried out on women attending at Shar –Ara teaching hospital in Kabul from 1th January 2020 -1th January 2021.In general, this study included 170 women with postpartum hemorrhage out of these 105 (61.8%) of whom had uterine atony, followed by other causes retained placenta tissue 22.4%, genital tract tears 14.7%, coagulopathies at 1.2%. It was found that 53.3% of patients were between 20-28 years old, 43.8% women were grand multipara, 87,6% cases were seen in full term pregnancies while 9.5% in post term pregnancies. 92.4% of women were found with previous history of PPH. Finally 47.6% cases managed by uterotonic agents (Metergin + Misoprostol + Oxytocin), 13.3% - only by Misoprostol, 10.5% - by Oxytocin + Misoprostol are used. B lynch compression sutures and uterine courage and massage was performed in 9,5% cases while 1.9% total abdominal hysterectomy was performed.In our study the frequency of uterine atony due to postpartum hemorrhage was found in 61.8% of cases. Most cases have been seen in women with full term gestational age, and Uterine atony is common in grand multipara, and young patients. Uterine atony mostly managed by uterotonic agents. Any delay in diagnosis and managements of PPH lead to maternal death and disability.